Green banking initiatives as catalyst for demonetization chaos – A study with reference to ICICI Bank - Uma Maheswari, G.U.; Sundaram, N.; Rengasamy, Dhanuskodi (2017)
This paper investigates the difference between the perceptions of users and non-users of internet banking. The main aim of demonetization is to dishearten the cash dependent economy. This article examined the opinion on demonetization and its effects. This study employed a quantitative approach on ICICI bank customers having salary account with this bank. Approached salary account holders of this bank in select colleges and investigated that internet banking is easy to use, reliable, convenient, safer, hassle free. Researcher observed that there is noteworthy disparity between users and non-users of green baking initiatives. Even though the account holders are having internet banking facility the study enquired that they are using this facility for transactions and to know the opinions for not adopting the facility. This article highlights the importance of activating and using internet banking to promote cash less transaction. The expected results might provide a clear view to the non-users regarding factors to use internet banking. The authors employ SPSS to analyze the opinion and awareness among the customers of the bank.